The bundengan of Wonosobo, Indonesia - Hamdan, Sinin; Mohamad Said, Khairul Anwar; M. Duin, Ezra A.; Sinin, Aaliyawani E. (North Carolina State University, 2024)
The bundengan is a unique traditional musical instrument with plucked strings from Wonosobo, Central Java, Indonesia. It can produce sounds that imitate the gong (i.e., a part of the gamelan instrument). The bundengan was initially constructed by duck herders as a means of shielding themselves from inclement weather while caring for their flocks. They also engage in musical activities and singing. The distinctive sound of the bundengan is created by plucking a set of strings fitted with tiny bamboo clips using the right hand and three elongated, slender bamboo blades with the left hand. The sound effect is produced by the bandulan, a small piece of bamboo attached to the string. The tuning of the bundengan depends on the player’s instinct. This study analyzed the pitch and timbre of the bundengan strings. Using Fast Fourier Transform (FFT), the sound from a plucked string yields the frequency spectrum of the actual vibrations from the strings. The results were used to validate the frequency as heard. The results showed that the pitch from the measured frequencies is not similar to the pitch as heard. The bundengan is tuned to a pitch corresponding to the timbre rather than a specific pitch.